Two hidden taxa in the Japanese encephalitis vector mosquito, Culex tritaeniorhynchus, and the potential for long-distance migration from overseas to Japan - Arai, Satoru; Kuwata, Ryusei; Higa, Yukiko; Maekawa, Yoshihide; Tsuda, Yoshio; Roychoudhury, Sudipta; Bertuso, Arlene Garcia; Phong, Tran Vu; Yen, Nguyen Thi; Etoh, Tomoki; Otuka, Akira; Matsumura, Masaya; et al. (PLoS neglected tropical diseases, 2022)
The Culex vishnui subgroups, particularly Culex tritaeniorhynchus , are considered the primary vectors of the Japanese encephalitis virus (JEV) in Asia. Recent molecular phylogenetic analyses of JEV isolates from Asian countries have shown that JEVs with diverse genetic variants are present in Asia. Furthermore, some JEV strains have been found to have crossed the East China Sea and been introduced into Japan. In this study, the possibility of overseas migration of the JE vector mosquito, Cx . tritaeniorhynchus was examined from the genetic, physical, and meteorological perspectives. Molecular phylogenetic analysis was performed based on both whole coding sequences and on the barcoding region of the mitochondrial cytochrome c oxidase subunit I ( COI ) gene of Cx . vishnui subgroups collected from Asian countries. Culex tritaeniorhymchus was classified into two genetically independent taxa by COI sequences: the Japanese type ( Ct -J), which inhabits Japan except for the Amami Islands of southern Japan, and the continental type ( Ct -C), which inhabits the Asian region except for Japan. It was confirmed that approximately 10% of Cx . tritaeniorhynchus trapped during the summer in western Kyushu were Ct -C, and that they could fly for up to 38 h continuously. The meteorological analysis also confirmed that the atmospheric flow occurring over the continent coincided with the date of Ct -C capture. This is the first report showing the existence of two taxa in Cx . tritaeniorhynchus . Their physical and physiological characteristics suggest the possibility of long-distance migration from overseas regions to Japan across the East China Sea. Future efforts are expected to provide evidence to support the occurrence of long-distance migration of Cx . tritaeniorhynchus with JEV.